Research at Small Canadian Universities - Owen, Michael (Canadian Journal of Higher Education, 1992)
Research in Canadian universities has received much attention in recent years. Governments and research councils have encouraged greater communication between industry and university researchers. Recently research councils, university administrators, and university faculty have focused their attention on improving the research environment in small universities. In the paper, the author outlines some of the issues that are deemed important to the conduct of research by faculty at small universities in English Canada. The paper is based on six years’ experience as a research administrator at a small university, and on a survey of research administrators, including vice-presidents academic and deans of graduate studies who had research as part of their daily responsibilities. The research was presented initially at the 1988 CAURA meetings. In this paper, some of the issues that are important to the conduct of research at small Canadian universities are outlined.